Developmental origins and evolution of pallial cell types and structures in birds - Zaremba, Bastienne; Fallahshahroudi, Amir; Schneider, Céline; Schmidt, Julia; Sarropoulos, Ioannis; Leushkin, Evgeny; Berki, Bianka; Van Poucke, Enya; Jensen, Per; Senovilla-Ganzo, Rodrigo; Hervas Sotomayor, Francisca; Trost, Nils; et al. (Science, 2025)
Innovations in the pallium likely facilitated the evolution of advanced cognitive abilities in birds. We therefore scrutinized its cellular composition and evolution using cell type atlases from chicken, mouse, and nonavian reptiles. We found that the avian pallium shares most inhibitory neuron types with other amniotes. Whereas excitatory neuron types in amniote hippocampal regions show evolutionary conservation, those in other pallial regions have diverged. Neurons in the avian mesopallium display gene expression profiles akin to the mammalian claustrum and deep cortical layers, while certain nidopallial cell types resemble neurons in the piriform cortex. Lastly, we observed substantial gene expression convergence between the dorsally located hyperpallium and ventrally located nidopallium during late development, suggesting that topological location does not always dictate gene expression programs determining functional properties in the adult avian pallium.